A projection of the expected wave power in the Black Sea until the end of the 21st century. (November 2020) - Rusu, Liliana
Abstract: The objective of the present work is to analyse until the end of the 21st century the dynamics of the wave power in the Black Sea in the context of climate changes. A wave modelling system was implemented for the entire basin of the Black Sea. The wind fields provided by a regional climate model for two emission scenarios are considered to force the wave model. Assuming both scenarios, wave simulations were carried out for the period 2071–2100 (distant future). Analyses of the wave power are performed over the entire basin and in eight reference points. The impact of climate change on the wave power in the Black Sea is estimated by performing comparisons with the previous results obtained for the near future (2021–2050) and historical (1976–2005) periods. The same wave modelling system and the wind data coming from the same regional climate model were considered in all periods. In this way, a comprehensive picture of the expected wave power dynamics in the basin of the Black Sea is provided. For the distant future, the changes in terms of the mean wave power are characterized by decreases for both scenarios. Highlights: Wave model simulations have been performed until the end of the 21st century. Wave energy assessment for distant future (2071–2100) was made. Evaluation of the wave power dynamics in the basin of the Black Sea is performed. Two emission scenarios are considered.